Axial Performances of CFRP-PVC Confined RAC Columns: Experimental and Numerical Study - Zidong Hu; Ruoyu Cao; Qiaoyun Wu; Cheng Zhao; Jie Li; Xuyong Chen (Buildings, 2025)
The use of recycled aggregate concrete (RAC) in construction mitigates environmental pollution by repurposing demolition waste, but its lower compressive strength compared to natural aggregate concrete (NAC) limits broader application. Although carbon fiber reinforced polymer (CFRP) composites and polyvinyl chloride (PVC) tubes have individually been shown to improve concrete strength and ductility, existing studies focus on fully wrapped CFRP jackets on NAC columns and do not systematically explore CFRP–PVC hybrid confinement using strips on RAC. To address this research gap, this study investigates the axial compressive behavior of CFRP–PVC–RAC columns by varying CFRP strip width (from 25 to 75 mm), strip spacing (from 31 to 77.5 mm), and the number of CFRP layers (one to nine) over a central PVC tube. Axial compression tests reveal that specimens with a central CFRP strip width equal to or greater than 75 mm achieve peak loads up to 1331 kN and that, after rupture of the central strip, the remaining strips continue to carry load, producing a more gradual stress–strain decline and enhanced ductility compared to fully wrapped controls (peak load 1219 kN). These results show that CFRP–PVC composites enhance the axial compressive strength and ductility of RAC columns. The confinement mechanism increases the ultimate axial strain and redistributes transverse stresses, delaying brittle failure and improving deformation capacity. When two or more CFRP layers are applied, strip width and spacing affect axial stress by no more than three percent. Increasing layers from one to four raises axial strength by approximately 23 percent, whereas adding layers beyond four yields diminishing returns, with less than a six percent increase. Finally, a multilayer lateral confined pressure formula is derived and validated against thirty-two specimens, exhibiting errors no greater than three percent and accurately predicting effective confinement. These findings offer practical guidance for optimizing strip dimensions and layering in CFRP–PVC reinforcement of RAC columns, achieving material savings without compromising performance.